12-(3,4,5-Trimethoxyphenyl)-2,3,4,12-tetrahydro-1H-5-oxatetraphen-1-one: crystal structure and Hirshfeld surface analysis - Jotani, Mukesh M.; Iniyavan, P.; Vijayakumar, V.; Sarveswari, S.; Tan, Yee Seng *; Tiekink, Edward R. T. * (International Union of Crystallography, 2016)
In the title compound, C26H24O5, the pyran ring has a flattened-boat conformation, with the 1,4-related ether O and methine C atoms lying 0.1205 (18) and 0.271 (2) Å, respectively, above the least-squares plane involving the doubly bonded C atoms (r.m.s deviation = 0.0208 Å). An envelope conformation is found for the cyclohexene ring, with the flap atom being the middle methylene C atom, lying 0.616 (2) Å out of the plane defined by the remaining atoms (r.m.s. deviation = 0.0173 Å). The fused four-ring system is approximately planar, with the dihedral angle between the least-squares planes through the cyclohexene and naphthyl rings being 10.78 (7)°. The trisubstituted benzene ring occupies a position almost perpendicular to the pyran ring [dihedral angle = 83.97 (4)°]. The most prominent feature of the packing is the formation of zigzag supramolecular chains mediated by aryl-C-H...O(methoxy) interactions; chains are connected into a three-dimensional architecture by methylene- and methyl-C-H...[pi] interactions. The prevalence of C-H...O and C-H...[pi] interactions is confirmed by an analysis of the Hirshfeld surface. A comparison with related structures suggests that the molecular conformation of the title compound is relatively robust with respect to varying substitution patterns at the methine C atom of the pyran ring.